Transcription factor GATA6 promotes migration of human coronary artery smooth muscle cells in vitro - Alajbegovic, Azra; Daoud, Fatima; Ali, Neserin; Kawka, Katarzyna; Holmberg, Johan; Albinsson, Sebastian (Frontiers in Physiology, 2022)
Vascular smooth muscle cell plasticity plays a pivotal role in the pathophysiology of vascular diseases. Despite compelling evidence demonstrating the importance of transcription factor GATA6 in vascular smooth muscle, the functional role of GATA6 remains poorly understood. The aim of this study was to elucidate the role of GATA6 on cell migration and to gain insight into GATA6-sensitive genes in smooth muscle. We found that overexpression of GATA6 promotes migration of human coronary artery smooth muscle cells in vitro, and that silencing of GATA6 in smooth muscle cells resulted in reduced cellular motility. Furthermore, a complete microarray screen of GATA6-sensitive gene transcription resulted in 739 upregulated and 248 downregulated genes. Pathways enrichment analysis showed involvement of transforming growth factor beta (TGF-β) signaling which was validated by measuring mRNA expression level of several members. Furthermore, master regulators prediction based on microarray data revealed several members of (mitogen activated protein kinase) MAPK pathway as a master regulators, reflecting involvement of MAPK pathway also. Our findings provide further insights into the functional role of GATA6 in vascular smooth muscle and suggest that targeting GATA6 may constitute as a new approach to inhibit vascular smooth muscle migration.